Inovasi Pengelolaan Limbah Sampah Rumah Tangga melalui Pemberdayaan Ekonomi Kreatif di Desa Sihite II - Arie Satria Tama; Tasya Umaira; Erika Rahmadani; Nadia Sari Situmorang; Rholand Muary (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2026)
The problem of household waste management in Sihite II Village has become an environmental issue impacting public health and the aesthetics of the area. Lack of public awareness of waste sorting and limited waste management facilities lead to the annual accumulation of plastic and organic waste. This Community Service Program (KKN) aims to provide education and direct implementation of waste management through the creation of ecobricks and biopore infiltration holes as an environmental solution and creative economic opportunity. The implementation method uses a community empowerment approach that includes outreach, training, practice, and evaluation. Results indicate that the implementation of ecobricks can reduce the volume of plastic waste by an average of 30–48% per household, while the application of biopores reduces organic waste by up to 40% and produces organic fertilizer. Economically, ecobricks have the potential to become a valuable product, selling for Rp3,500–Rp7,000 per unit, and can be used to make furniture or crafts with higher economic value. This program demonstrates that community empowerment-based waste management not only has an environmental impact but also opens up sustainable creative economic opportunities for the people of Sihite II Village.